Respiratory Viral and Bacterial Factors That Influence Early Childhood Asthma - Mthembu, Nontobeko; Ikwegbue, Paul; Brombacher, Frank; Hadebe, Sabelo (Frontiers in Allergy, 2021)
Asthma is a chronic respiratory condition characterised by episodes of shortness of breath due to reduced airway flow. The disease is triggered by a hyperreactive immune response to innocuous allergens, leading to hyper inflammation, mucus production, changes in structural cells lining the airways, and airway hyperresponsiveness. Asthma, although present in adults, is considered as a childhood condition, with a total of about 6.2 million children aged 18 and below affected globally. There has been progress in understanding asthma heterogeneity in adults, which has led to better patient stratification and characterisation of multiple asthma endotypes with distinct, but overlapping inflammatory features. The asthma inflammatory profile in children is not well-defined and heterogeneity of the disease is less described. Although many factors such as genetics, food allergies, antibiotic usage, type of birth, and cigarette smoke exposure can influence asthma development particularly in children, respiratory infections are thought to be the major contributing factor in poor lung function and onset of the disease. In this review, we focus on viral and bacterial respiratory infections in the first 10 years of life that could influence development of asthma in children. We also review literature on inflammatory immune heterogeneity in asthmatic children and how this overlaps with early lung development, poor lung function and respiratory infections. Finally, we review animal studies that model early development of asthma and how these studies could inform future therapies and better understanding of this complex disease.